On maternity and the stronger immune response in women - Evan Mitchell; Andrea L. Graham; Francisco Úbeda; Geoff Wild (Nature Communications, 2022)
Women generally mount a stronger immune response to infections than men do, resulting in a higher impact of autoimmune diseases. Here, the authors show that pathogen transmission from mother-to-child during pregnancy drives the co-evolution of a stout defence against harmless pathogens in women.